Lysosomal‐associated transmembrane protein 4B regulates ceramide‐induced exosome release. Issue 12 (8th October 2020) - Yuyama, Kohei; Sun, Hui; Mikami, Daisuke; Mioka, Tetsuo; Mukai, Katsuyuki; Igarashi, Yasuyuki
Abstract: Exosomes are extracellular vesicles that mediate the transport of intracellular molecules, including neurodegenerative agents. Exogenously administrated ceramides have been implicated in the acceleration of exosome production by neurons; however, the molecular machinery involved in this process is unknown. Here, we found that ceramides, especially those consisting of long fatty acids, were internalized into the endocytic pathway in neuroblastoma SH‐SY5Y cells to induce exosome secretion through lysosome‐associated protein transmembrane 4B (LAPTM4B). Knockdown of LAPTM4B inhibited the ceramide‐mediated increase in exosome release completely. Fluorescence microscopy observations indicated that exogenous ceramides promote the transport of multivesicular bodies to the plasma membranes in a LAPTM4B‐dependent manner. Similarly, inhibition of acid ceramidase, which tends to induce intracellular ceramide accumulation, increased exosome production by SH‐SY5Y cells in a LAPTM4B‐dependent manner. Furthermore, the level of amyloid‐ß protein (Aß) was decreased in neuronal cells following treatment with exogenous ceramide or inhibition of acid ceramidase, and this effect was attributed to the LAPTM4B‐dependent efflux of Aß‐containing exosomes. Overall, these findings reveal the novel machinery involved in exosome secretion regulated by ceramides and LAPTM4B, and may contribute to efforts to ameliorate the cellular accumulation of neurodegenerative agents such as Aß.